Exit regime for international students: The case of Georgia - Krannich, Sascha; Hunger, Uwe; Justus Liebig University Giessen (My University, 2022)
In this paper, we focus on an exit regime for an important and fast rising, but still under-researched form of migration: student migration. More and more countries in the Global South—which suffered large emigration numbers of students to the Global North in the past—have started to establish their own exit regimes to regulate student emigration in their own interests. How do these exit regimes for students studying abroad operate? And are they actually successful in regulating student migration in the interest of the emigration state? Here, we take a closer look at the exit regime of the Caucasian state of Georgia. Drawing on Krasner's regime theory and on a larger empirical study, we identified a sophisticated exit regime of the Georgian state that operates on the basis of various scholarship programmes for Georgian students who study abroad and who have to return to Georgia after graduation.
Keywords: ddc:610